دور النخبة السياسية في التغيير الإجتماعي - نصرالله, واحدة حمةويس (Sulaimani Journal for Humanities, 2021)
The research is considered from theoretical research, is an attempt to clarify the role that the political elite can play on the process of social change. The research consists of four sections: the first topic includes the general framework of the research and the most important concepts contained in it. The second topic is devoted to the elite and includes the historical roots of the elite concept, trends, elite analysis and their characteristics. The third topic includes social change. Forth topic devoted to the role of elite in social change, as well as conclusions and recommendations. The research has come up with several results, the most important of which are:1-Societies cannot be rolled and governed by one person, for he will remain important without the presence of a class working to impose respect for his orders and their implementation .2- The political elite is the ruling class that maintains the balance of society and holds the rein of affairs.3- The political elite reject the idea of rotating power and exercises maximum coercion over the opponents.4-The Arabic and Eastern world has no succeeded in creating a political elite that enjoys popular acceptance.5-The worst disadvantages of political elite in the Middle East are that it helps to personalize authority. 6-In the Arab and Eastern world, and the political elite exercises tyrannical rule.7-The political elite is generally subject to the laws of change, according to the variable in the environment in which it is located.8-Resistance to change appears on the part people who cheat on the demise of their interests.